TINJAUAN PROSEDUR LELANG NON EKSEKUSI SUKARELA SECARA TIDAK LANGSUNG DI BALAI LELANG PT TRIAGUNG LUMINTU - , Yullinta Astried Dian Vitalova ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to find out about non-execution of a voluntary and indirectly auction procedure on the auction house of PT Triagung Lumintu and to find out what the advantages and disadvantages of non execution of a voluntary and indirectly auction procedure that have been implemented by the auction house of PT Triagung Lumintu.. This research is a normative juridical study of the data examined, studied and developed based on literature data. Its used secondary data and supported by primary data. The secondary data obtained through library research consisted of primary legal materials, secondary and tertiary. While the primary data obtained through field research in the form of interviews with informants and respondents. The data have been collected were analyzed qualitatively and arranged in a descriptive report. The results showed that the implementation of the non execution of voluntary and indirectly auction in the auction house PT Triagung Lumintu has met most of the core values and essence of the principle of the auction, unless the principle of efficiency. This auction also meet the applicable provisions in the rules of the auction, so its legal. Non execution of voluntary and indirectly auctions use most of the auction mechanism in general, except for offering media using information technology. Non execution of voluntary and indirectly auctions has several advantages compared with the auction in general that does not require the physical presence of the bidders so as to save time, effort and cost because it has no geographic limitations. otherwise it does not require substantial capital to place a an auction. non-execution of voluntary and indirectly auctions also have weaknesses, among others, namely the lack of adequate facilities and infrastructure, lack of security in the interaction, not human resources master information technology, high cost of providing software and hardware, as well as the lack of regulations regarding voluntary auction resulted in non executable development of non-execution of voluntary and indirectly auctions in Indonesia is hampered.